IMPLEMENTASI METODE DISCOVERY LEARNING DALAM PEMBELAJARAN AKIDAH AKHLAK DI MTS NURUL QOMAR PEKALONGAN - Faiqotul Mutia; Fatmawati Nur Hasanah; Arditya Prayogi (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
Interesting and enjoyable learning methods have a big influence on the learning atmosphere in the classroom. Therefore, teacher strategies are needed in the learning process, one of which is by implementing appropriate learning methods or models to support the sustainability of effective learning. One of the models used is discovery learning. This study is classified as qualitative research that uses data collection methods through observation, interviews, and documentation. The results of the study indicate that the application of discovery learning in the subject of Aqidah Akhlak at MTs Salafiyah Nurul Qomar Pekalongan is carried out through three main stages. First, preparation for the implementation of the discovery learning model, which includes making lesson plans, compiling syllabuses, and providing handbooks and materials that are ready to use. Second, the implementation of learning is carried out in three stages. In the preliminary stage, the activity begins with the teacher greeting, conveying learning objectives, and providing apperception. In the core stage, students are given stimulus to identify problems, collect data, process data, prove, and draw conclusions (generalization). The closing stage is carried out by giving appreciation to the results of student work, accompanied by final motivation from the teacher. Third, learning evaluation is an indicator of the success of implementing this model, which is evident from the significant increase in student grades. The application of the discovery learning method has been proven to improve students' learning process in terms of knowledge, attitudes, and motor skills. This model also provides students with broader insights. Therefore, consistent application of discovery learning is highly recommended so that students are accustomed to thinking critically, finding new solutions, and exploring problems better.